Countering Disinformation: The Role of Civic Education in the Post-Truth Era - Irfandi Irfandi (Yayasan Insan Mulia Bima, 2026)
The rapid advancement of digital technology has transformed information threats from mere disinformation into an epistemic crisis, characterized by the declining ability of society to evaluate and verify the credibility of information. This study aims to analyze this transformation, examine the reorientation of Civic Education as an instrument of epistemic defense, and formulate implementation strategies through the integration of critical literacy into the curriculum. This study employed a qualitative descriptive literature review approach by analyzing scholarly articles, books, reports from international organizations, and relevant policy documents. Data were analyzed through reduction, synthesis, and interpretation of the reviewed literature. The findings reveal that the epistemic crisis is driven by the proliferation of disinformation, the rapid development of artificial intelligence, social media algorithms, and the echo chamber phenomenon, all of which erode public trust in credible sources of knowledge. These conditions necessitate a reorientation of Civic Education from a normative citizenship paradigm toward strengthening epistemic defense through critical thinking, information evaluation, and evidence-based reasoning. This reorientation can be implemented by systematically integrating critical literacy into learning outcomes, instructional materials, inquiry- and project-based learning strategies, and authentic assessment. The study concludes that integrating critical literacy into Civic Education is a fundamental strategy for fostering citizens with epistemic resilience who are capable of critically evaluating information and participating responsibly in democratic life in the digital era.